Osteonecrosis of the jaw in patients with multiple myeloma treated with bisphosphonates: Evidence of increased risk after treatment with zoledronic acid - Dimopoulos, M.A.; Kastritis, E.; Anagnostopoulos, A.; Melakopoulos, I.; Gika, D.; Moulopoulos, L.A.; Bamia, C.; Terpos, E.; Tsionos, K.; Bamias, A. (Haematologica, 2006)
Osteonecrosis of the jaw (ONJ) has been associated with the use of pamidronate and zoledronic acid. ONJ was assessed prospectively since July 2003 in 202 patients with multiple myeloma (MM) who received bisphosphonates since April 1995. Fifteen patients (7.4%) developed ONJ. The median time of exposure to bisphosphonates was 39 months for patients with ONJ compared to 28 months (p=0.048) for patients with no ONJ. The cumulative hazard of developing ONJ was significantly higher in patients treated with zoledronic acid alone than in those treated with pamidronate alone/pamidronate+zoledronic acid/zoledronic acid+ibandronate sequentially (1% at 1 year and 15% at 4 years vs. 0% and 5%, p=0.003). In conclusion, the risk of ONJ is increased with time of exposure and probably with the use of zoledronic acid. ©2006 Ferrata Storti Foundation.
Keywords: Bisphosphonates; multiple myeloma; Osteonecrosis; Zoledronic acid